Cultivation of Digitalis lanata Ehrh in Chamba hills Himachal Pradesh - Gupta, Rajendra (Indian Forester, 1967)
The natural glycoside-Lanatoside C and it. De-acetyl derivative Digoxin, obtained from leavea of Digitalis lanata Ehrh , are most efficaceous cardio-tonic drug that find increasing, use in modern cardio-therapy. The plant, though introduced in the country long back is nowhere grown on commercial scale and hence India's requirements of the glycoside continues to be Imported in toto. The author has carried out experiments for four consecutive years on different aspects of its farming in Chamba district, H.P.;the leaves so produced are found acceptable to Pharmaceutical industry. Cultural details For commercial cultivation of this species in India are presented.